HUBUNGAN KEPEMIMPINAN, MOTIVASI DAN KOMPENSASI TERHADAP KEPUASAN KERJA PERAWAT RAWAT INAP RSUD TALUK KUANTAN KABUPATEN KUANTAN SINGINGI TAHUN 2017 - NURUL KHIKMAH HAYRANI MANIHURUK (LP2MTBM MAKARIOZ, 2018)
The prolem at the Teluk Kuantan Singingi Hospital is there a gap between nurse job satisfaction with leadership of the headroom, nurse work motivation and nurse work compensation. If this problem is allowed continue of course will give further impact, that is decreased of hospital services quality in service delivery to the commuity. So this research was conducted with the aim to know